Influence of operational factors on the patterns of distribution of discrete deformations of the surface layer of metal structures for multi-cycle loading of samples - Mailo, A. M.; Pysarenko, G. G.; Voinalovych, O. V. (Mechanics and Advanced Technologies, 2018)
The structural material heterogeneity causes the scatter in the mechanical properties. The local stresses in the crystallite can exceed by several times the actual stress values. The order of magnitude of the microplastic strains is 10-6 mm/mm, which is below the fatigue limit at normal stresses. Due to the structural and technological factors, the surface elasto-plastic layer of the structural material is less resistant to mechanical damage than the bulk of the material, resulting in a certain number of fatigue failure cases in the total number of failures of metal structures. Non-uniformities in the micro-stress state lead to an irregular development of micro-plastic strains, whose localization affects the evolution of a dissipative structure in a polycrystalline material, which is particularly critical for the subsurface layer. The analysis of the damage state evolution for structure-sensitive parameters of the substructure surface makes it possible to control the mechanical properties of the structural material under high-cycle deformation